Digital Zuhd from the Qur'anic Perspective - Muhammad Nur Akbar Lubis (Sufiya Journal of Islamic Studies, 2026)
In the age of social media, flexing (the public display of wealth and material success) has emerged as a contemporary social pathology. This study aims to analyze the phenomenon of flexing through the Qur’anic concept of zuhd (ascetic detachment) and to formulate its ethical implications and resolutions within the context of modern digital life. Employing a thematic (maudhu‘i) library research approach, the study draws primarily on Hamka’s Tafsir Al-Azhar and M. Quraish Shihab’s Tafsir Al-Misbah, complemented by relevant secondary literature. The findings reveal that the Qur’anic notion of mukhtāl signifies visual manifestations of arrogance expressed through material symbols and status displays, whereas fakhūr refers to verbal self-glorification aimed at gaining social recognition. These concepts demonstrate a strong correspondence with contemporary flexing practices, which are closely linked to social comparison mechanisms and may contribute to adverse psychological consequences, including Fear of Missing Out (FOMO). As its principal contribution, this study proposes the concept of digital zuhd, understood not as a rejection of technology but as the capacity to maintain psychological and spiritual autonomy amid the pressures of digital culture. The implementation of digital zuhd is grounded in three fundamental pillars: rejecting the pursuit of validation through digital metrics, cultivating social empathy in the public display of personal blessings, and reorienting social media toward the dissemination of collective benefit. This recontextualization offers an alternative paradigm for the development of Islamic digital ethics while simultaneously contributing to the promotion of mental well-being in cyberspace.